Development of label-free biosensor for the detection of adenosine diphosphate as a universal kinase/atpase assay using nanoimprinted flexible two-dimensional photonic crystal - Endo, T.; Henares, Bernadette; Hisamoto, H. (Chemical and Biological Microsystems Society, 2012)
The use of photonic crystals (PC) as biosensors for label-free detection of kinase activity is presented. Here, we exploited the unique optical properties of PC to detect enzymatic reactions using Protein Kinase A (PKA) as model system. Detection of one of the reaction products, adenosine diphosphate (ADP) was achieved with sufficient sensitivity using nanoimprinted flexible two-dimensional PC (2D-PC) without the use of tags or dyes. This assay offers a rapid, simple and cost-effective method which can be used as a universal assay procedure to detect kinase reactions.